PERILAKU STRES JALUR UJI TRIAKSIAL PADA TANAH LEMPUNG KARAWANG - puspa ningrum (LPPM Universitas Abdurrab, 2019)
Generally, laboratory testing to determine the value of soil shear strength and stress path is triaxial test, especially for clay soil. In this research, the clay used for digital triaxial testing on axial compression (AC) stress path is Karawang clay soil, West Java, which have high plasticity (CH) in USCS classification. On pre-saturation process, a combination of vaccum and back pressure is used to speed up the saturation of the sample and to provide a high degree of saturation. Furthermore, the obtained soil parameters are used as inputs on finite element modeling which Mohr Coloumb and Hardening Soil model were used as the soil constitutive models. The results show that parameter optimization using hardening soil modeling has a behavior that is closer to the shape of the stress strain curve from laboratory tests.